Exploring public perception of environmental technology over time - Carola Braun; Katrin Rehdanz; Ulrich Schmidt (Kiel Institute for the World Economy (IfW), 2016)
Public opinion has a substantial impact on political actions. However, public opinion might be driven by temporary emotions. If these emotions cool off over time, public opinion might change as well. This paper analyses how emotions drive public opinion over time for the case of an environmental climate engineering technology, namely solar radiation management (SRM). SRM is a possible strategy to fight climate change by injection of sulphate aerosols into the stratosphere. Its potential implementation involves major risks and faces strong public opposition. Using panel survey data, we show that most respondents initially show strong negative emotions towards SRM and reject the technology. However, emotions cool off over time and acceptance increases. The increase in acceptance is larger, the longer the cooling-off period between two surveys is.
Keywords: Q54; Q55; D80; H40; 330; Public perception; social movements; Climate engineering; Cooling-off